PERTUMBUHAN VEGETATIF BROWN MIDRIB (BMR) SORGUM PADA TINGKAT NAUNGAN BERBEDA DAN KEPADATAN POPULASI - Kaligis, Yohanes Barry; Kaunang, Ch. L; Kaligis, D A; -, Rustandi - (ZOOTEC, 2017)
ABSTRACT VEGETATIVE GROWTH OF BROWN MIDRIB (BMR) SORGHUM ON THE DIFFERENT LEVELS SHADE OG SHADE AND POPULATIONS DENSITY. The present study was conducted to determine the effect of shading area and plant population density and their interaction on vegetative growth of Brown Midrib (BMR) Sorghum. A Completely Randomized Design (CRD) in a Factorial arrangement with 2 factors of nitrogen level and shading area, as follows: factor A = shading area of A1 = no shading area (0%), and N2 = shading area; whereas factor B = plant population density of B1 = 4 plants, B2 = 6 plants, B3 = 8 plants, and B4 = 10 plants. Variables measured were: leaves number, plant height, and the correlation between leaves number and plant population density. Research results showed that plant height in open area (no shading) was about 86.33 cm and significantly higher (P < 0.05) compared to other treatments. Leaves number in open area was about 7.55 sheats and significantly higher (P < 0.05) compared to other treatments. It can be concluded that shading positively decreased or retarded Brown Midrib (BMR) Sorghum growth as indicated by lower plant heights in shading area. In a limited daylight, plants needs an adaptation period to fulfill their needs for photosyntesis processes. Â  Key words: brown midrib (BMR) sorghum, growth, population density, shading